Structure and mechanism of glutamate racemase from Aquifex pyrophilus - Hwang, KY; Cho, CS; Kim, SS; Sung, HC; Yu, YG; Cho, YJ (NATURE PUBLISHING GROUP, 1999)
Glutamate racemase (MurI) is responsible for the synthesis of D-glutamate, an essential building block of the peptidoglycan layer in bacterial cell walls. The crystal structure of glutamate racemase from Aquifex pyrophilus, determined at 2.3 Angstrom resolution, reveals that the enzyme forms a dimer and each monomer consists of two alpha/beta fold domains, a unique structure that has not been observed in other racemases or members of an enolase superfamily, A substrate analog, D-glutamine, binds to the deep pocket formed by conserved residues from two monomers. The structural and mutational analyses allow us to propose a mechanism of metal cofactor-independent glutamate racemase in which two cysteine residues are involved in catalysis.
Keywords: COMPLETE GENOME SEQUENCE; AMINO-ACID RACEMASE; MANDELATE RACEMASE; CATALYTIC RESIDUES; CRYSTAL-STRUCTURE; ALANINE RACEMASE; CARBON ACIDS; ACTIVE-SITE; PROTEIN; IDENTIFICATION